1999
DOI: 10.1017/s0885715600010526
|View full text |Cite
|
Sign up to set email alerts
|

Crystal chemistry of (RE, A)2M3O7 compounds (RE=Y, lanthanide; A=Ba, Sr, Ca; M=Al, Ga)

Abstract: Phases of general formula (RE,A) 2 M 3 O 7 (RE=lanthanide, A=Ca, Sr, Ba; M=Ga, Al) are of interest for their nonlinear optical properties and have potential as solid state lasers. Their structures have been refined using X-ray and neutron diffraction data and are related to gehlenite, Ca 2 Al 2 SiO 7 , with M cations occupying Al and Si sites and RE and A cations sharing the Ca site with no evidence for ordering, although they occur in the ratio 1:1 because of stoichiometry; the M cations are tetrahedrally coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 19 publications
4
48
0
Order By: Relevance
“…A CA single phase was observed up to 2 mol% Eu 2+ , while EuCaAl 3 O 7 secondary phase appeared at 6 mol% Eu 2+ and gradually increased by adding more Eu 2+ ions. It was reported that EuCaAl 3 O 7 could be formed by the reaction of calcium mono aluminate and europium aluminate by solid-state reaction at 1300-1400 • C [17]. In this experiment, europium concentrations PL intensity (Fig.…”
Section: Resultssupporting
confidence: 49%
“…A CA single phase was observed up to 2 mol% Eu 2+ , while EuCaAl 3 O 7 secondary phase appeared at 6 mol% Eu 2+ and gradually increased by adding more Eu 2+ ions. It was reported that EuCaAl 3 O 7 could be formed by the reaction of calcium mono aluminate and europium aluminate by solid-state reaction at 1300-1400 • C [17]. In this experiment, europium concentrations PL intensity (Fig.…”
Section: Resultssupporting
confidence: 49%
“…The experimental crystal structures of the stoichiometric parent compound [22] and the oxygen excess [13] compound were used as the initial structures for modeling. Interatomic potentials and shell model parameters were transferred from previous work, [12,23] Table 1.…”
Section: Structural Modelingmentioning
confidence: 99%
“…1. 16 According to the peak 2 values in the XRPD pattern, the tetragonal unit cell parameters are calculated to be a = b = 7.972 Å, c = 5.251 Å. The structure of the as-grown crystal was studied by x-ray powder diffraction ͑XRPD͒, and results are shown in Fig.…”
Section: Crystal Growthmentioning
confidence: 99%